Military-industrial complexities, university research and neoliberal economy. (September 2016) - Smart, Barry
The article provides an analysis of the militarization of scientific research and the scale and consequences of military and defence-related research on university campuses in the United States and United Kingdom. It achieves this through an analysis of the historical background to the complex forms of articulation which have developed between the military, industry and university research. Particular consideration is given to developments in the United States from 1940, including concerns expressed about the impact of an expanding military-industrial complex on the conduct of research in universities. Drawing on critical social and historical research, the article analyses the relationship between universities and colleges and the institution of the military in the United States and the United Kingdom, the symbiotic relationship between neoliberalism and militarism, and, in addition, the consequences for the conduct of research in the natural sciences and the social sciences within universities.